PASCA KONFLIK SYARA YANG TERJADI DI KABUPATEN ACEH SINGKIL - Salamah Salamah (Pascasarjana UIN Sumatera Utara, 2021)
Human resources are the main component for the success of educational programs at universities in order to realize their vision and mission. Universities must have a complete human resource management system in accordance with planning and development needs. The complexity of the problem of PT requires quality resources to make PT as a diploma-giving institution that makes a full contribution to the issues or problems of the nation. Human resource quality development needs to be made so that it becomes a guideline for human resource management both at the university level and study programs by implementing a quality cycle in the form of planning, implementation, and monitoring-evaluation flows. Thus, the development of quality at the university level is expected to encourage the development of activities that are able to improve the quality of human resources both intellectually, academically and personally. This research on policy innovation for the development of quality lecturers at STAI Al-Hikmah Medan uses an interpretive/post positivistic paradigm with a qualitative approach. The meaning of the interpretive/post positivistic paradigm is that social reality is actually meaningful. according to the observations of researchers so far, there are still many obstacles and shortcomings, both in terms of planning and in the implementation and evaluation. Research findings regarding the implementation of lecturer quality development developed at STAI Al-Hikmah in innovation of lecturer quality development policies, including aspects of planning, implementation, evaluation and monitoring of lecturers still do not meet the standards, this can be seen from a number of phenomena that have surfaced (especially in STAI Al-Hikmah Medan) include: 1) the absence of a systematized lecturer development program starting from the acceptance of lecturers until the end of the lecturer's duties (retirement); 2) there is no more comprehensive knowledge grouping and identification of appropriate lecturer specializations.